Removal of taste and odour from potable water by ozone and Powdered Activated Carbon (PAC). (5th March 2010) - Andreadakis, Andreas D.; Mamais, Daniel; Gavalakis, Evina A.; Noutsopoulos, Constantinos; Kouris, Nikos; Nikitopoulos, Georgios
The paper presents experimental evidence that selection and addition of an appropriate type of Powdered Activated Carbon (PAC) and alternatively or in combination ozonation of the water can be very effective in removal of both geosmin and 2-MIB from surface waters intended for supplying potable water. According to the experimental results, it was shown that the adsorptive capacity of the carbon is about five times greater in the case of geosmin when compared with 2-MIB. Furthermore, addition of ozone at doses in the range 1-3 mg/L for a period of 5-10 min can reduce odour to levels below threshold odour value.